2010
DOI: 10.4314/ejesm.v3i1.54392
|View full text |Cite
|
Sign up to set email alerts
|

Morphometric Analysis of Ogunpa and Ogbere Drainage Basins, Ibadan, Nigeria

Abstract: The paper analysed the morphometric parameters of Ogbere and Ogunpa drainage basins located on basement complex rock in Southwestern Nigeria. Data used were generated from topographical map of Ibadan Northeast on scale 1:25,000 published by Federal Survey of Nigeria (1975). Result obtained indicated that studied basins exhibits high spatial variation in their morphometric properties. The study further revealed that morphometric properties of Ogunpa drainage basin are likely to induce high magnitude flood compa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
42
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 40 publications
(45 citation statements)
references
References 8 publications
3
42
0
Order By: Relevance
“…Though, Ukoghor is smaller in size, the basin has recorded more flood events in the city than Kereke drainage basin, which is larger in size. The reason for this as observed by [2] in their study of Ogbere and Ogunpa drainage basins can be traced to the difference in basin length. Kereke drainage basin is larger in size, a factor which affect its length (the larger the basin, the longer its length).…”
Section: Drainage Basin Areamentioning
confidence: 90%
See 4 more Smart Citations
“…Though, Ukoghor is smaller in size, the basin has recorded more flood events in the city than Kereke drainage basin, which is larger in size. The reason for this as observed by [2] in their study of Ogbere and Ogunpa drainage basins can be traced to the difference in basin length. Kereke drainage basin is larger in size, a factor which affect its length (the larger the basin, the longer its length).…”
Section: Drainage Basin Areamentioning
confidence: 90%
“…The choice of morphometric variables that were examined in this study was based on the result obtained from previous studies, which have been found to correlate highly with peak discharge, runoff volumes and sediment delivery [22]; [11]; [23]; [10]; [24]; [5] cited in: [2]. In all, eleven (11) morphometric variables (broadly categorized into three (3) vis; area, linear and relief morphometrics) as suggested by [2] were examined (Table 2 and 3).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations